The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/23746149.2020.1870559
|View full text |Cite
|
Sign up to set email alerts
|

Quantum control in open and periodically driven systems

Abstract: Quantum technology resorts to efficient utilization of quantum resources to realize technique innovation. The systems are controlled such that their states follow the desired manners to realize different quantum protocols. However, the decoherence caused by the system-environment interactions causes the states deviating from the desired manners. How to protect quantum resources under the coexistence of active control and passive decoherence is of significance. Recent studies have revealed that the decoherence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 223 publications
(284 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, the presence of Fe 2+ in the cathode chamber was confirmed using the phosphoric acid masking -potassium ferricyanide coloring method. [43] K 3 Fe(CN) 6 was employed to rapidly form Teng's blue precipitate upon reaction with Fe 2+ . H 3 PO 4 was added to the solutions before and after the photoreaction to promote the formation of a colorless complex between Fe 3+ and H 3 PO 4 , thereby eliminating interference from Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the presence of Fe 2+ in the cathode chamber was confirmed using the phosphoric acid masking -potassium ferricyanide coloring method. [43] K 3 Fe(CN) 6 was employed to rapidly form Teng's blue precipitate upon reaction with Fe 2+ . H 3 PO 4 was added to the solutions before and after the photoreaction to promote the formation of a colorless complex between Fe 3+ and H 3 PO 4 , thereby eliminating interference from Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, driven-dissipative quantum systems have recently attracted intensive research interests, particularly in the context of quantum control (for a very recent, comprehensive review, the reader is referred to Ref. 64 ). Generally, the steady state of such systems can be far from equilibrium because of the unavoidable competition between driving and dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the above-listed protocols, it has also long been confirmed that temporal periodic driving on the open system can impose significant effects on the system dynamics [36][37][38][39][40][41][42]. Some methods of dealing with this problem, e.g., spectral filtering theory [43][44][45][46][47] and those based on the Floquet theory [48][49][50], have also been developed. Different from the bound states generated in the time-independent system, e.g., the impurity system in the solid system, the bound states generated by temporal periodic driving fields are time-dependent and are dubbed as Floquet bound states [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Some methods of dealing with this problem, e.g., spectral filtering theory [43][44][45][46][47] and those based on the Floquet theory [48][49][50], have also been developed. Different from the bound states generated in the time-independent system, e.g., the impurity system in the solid system, the bound states generated by temporal periodic driving fields are time-dependent and are dubbed as Floquet bound states [48][49][50]. The conditions for their formation as well as their applications in the quantum information technologies are also discussed [48,50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation